Accesslaw annotations on Philippine statutes, v. 1 private law (the laws on private transactions and relations). - Accesslaw, Inc. (Firm). ([Manila] Accesslaw)
Volume 1 of the Laws Annotated series, this is a full-text database on laws that regulate private transactions and relations in the Philippines. It is divided into 8 topics: constitution, corporations, securities and commercial documents, labor, taxation and tariff, investments ; banking and finance ; persons and citizenship ; and insurance.
Keywords: Civil law -- Philippines; Philippines (Republic) -- Laws, statutes, etc; Annotations and citations (Law) -- Philippines